A woman called Sage : a novel - Mills, DiAnn (Zondervan, 2010)
Sage Morrow has lost everything she loved. Now, she is a Colorado bounty hunter determined to track down and bring killers to justice ... and it's personal. But when the tables are turned, will Sage become the one who is hunted? A high-energy historical romance novel set in the late 1800s.